Barriers and Facilitators to Lung Cancer Screening: A Physician Survey. Issue 7 (September 2022) - Lowenstein, Margaret; Karliner, Leah; Livaudais-Toman, Jennifer; Gregorich, Steven; Velazquez, Ana I.; Vijayaraghavan, Maya; Walsh, Judith M.E.; Kaplan, Celia P.
Purpose: To describe barriers to lung cancer screening (LCS) among family medicine and general internal medicine primary care physicians (PCPs) and assess the association of barriers with discussion and referral for screening. Design: Cross-sectional survey. Subjects and Settings: Random sample of primary care physicians (PCPs) in California. Measures: PCP practices for discussion and referral for LCS and ratings of LCS barriers. Analysis: We performed exploratory factor analysis to identify four barrier constructs: (1) Physician Visit-Level Barriers to screening referral; (2) Physician System and Evidence Barriers; (3) Patient Cost Barrier; and (4) Other Patient Barriers. We then performed multivariable logistic regression adjusted for physician and practice characteristics to assess the association between the physician-reported barriers and whether PCPs discussed or referred for LCS. Results: 368 physicians responded (response rate 42%). Most worked in large metropolitan areas (80%) and large health systems (59%). After adjusting for physician and practice characteristics, we found that physician-reporting of System and Evidence Barriers was associated with lower odds of discussion or referral for LDCT (aOR .18, 95% CI 0.09–0.37), while physician-reported Visit-Level Barriers were associated with increased odds discussion or referral (aOR 2.65, 95% CI 1.30–5.04). Conclusions: While physicians reported numerous barriers to LCS, we found that barriers were differentially associated with discussion or referral for screening. As new LCS guidelines broaden screening eligibility, it is critical to address these barriers to achieve higher rates of evidence-based LCS.